Intervenções cirurgicas (microfratura, perfuração, transplante osteocondral autologo e homologo) para o tratamento de lesões (osteo) condrais no joelho de adultos: revisão sistematica - Gracitelli, Guilherme Conforto [UNIFESP] (2016)
Introduction: Cartilage defects of the knee are often debilitating and predispose to osteoarthritis. Microfracture, drilling, mosaicplasty and allograft transplantation are four surgical treatment options that are increasingly performed worldwide. We set out to examine the relative effectiveness of these four different methods. Objective: To assess the effects (benefits and harms) of different surgical interventions (microfracture, drilling, mosaicplasty, and allograft transplantation) for treating isolated cartilage defects of the knee in adults. Methods: We searched the Cochrane Bone, Joint and Muscle Trauma Group Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, MEDLINE, SPORTDiscus, LILACS, trial registers and conference proceedings. Date of search: February 2016.Any randomised or quasi-randomised trials that evaluated surgical interventions (microfracture, drilling, mosaicplasty and allograft transplantation) for treating isolated cartilage defects of the knee in adults.At least two review authors independently selected studies, assessed risk of bias and extracted data. Intervention effects were assessed using risk ratios for dichotomous data and mean differences (MD) for continuous data, with 95% confidence intervals. Data were pooled using the fixed-effect model, where possible. Results: Three randomised controlled trials comparing mosaicplasty versus microfracture were included. These reported results for a total of 133 participants, of whom 79 (59%) were male. Mean ages in the three trials ranged between 24.4 and 32.3 years. All studies included cartilage lesion grade 3 or 4 (ICRS classification). The Defect area ranged from 1.0 to 6.0cm2. No trials of allograft transplantation or drilling were identified. All trials were judged as being at high or unclear risk for performance and reporting bias. Trials presented small sample size, with two studies in a single centre. Reflecting the imprecision of the results, the evidence was deemed to be of very low quality for all primary and secondary outcomes; which means that our level of uncertainty about the estimates is high. Data that assessed function were presented in all reports. Only one study (57 participants) found a clinically important difference in favour of mosaicplasty at one year (MD 10.29, 95% CI 7.87 to 12.71). This difference also continued at three years (mean 89 versus 75; reported P < 0.001) and at 10 years (MD 13.97, 95% CI 13.25 to 14.69). In the long-term (5 years and above), two trials pooled (72 participants) showed no clinically important difference between the two groups (MD -1.10, 95% CI -4.54 to 2.33). No trial found statistical or clinical difference of better long-term quality of life and pain symptoms. Pooled results for treatment failure reported at long-term follow-up in the three trials showed recurrence and re-operations were significantly fewer in the mosaicplasty group (10/64 versus 20/65; RR 0.47, 95% CI 0.24 to 0.90). The majority of failures were mainly due symptom recurrence. All trials reported activity score but due to clear statistical and clinical heterogeneity, we did not pool the long term Tegner score results. One study (57 participants) reported slightly higher Tegner score in intermediate-term (MD 0.48, 95% CI 0.21 to 0.75) and long-term (MD 0.72, 95% CI 0.46 to 0.98) in the mosaicplasty group, however between group difference may not be clinically important. Other two trials found no difference between the two groups for activity scores. Only one study reported and found a greater return to pre-injury level of sports activities in the higher mosaicplasty group (26/28 versus 15/29; RR 1.90, 95% CI 1.34 to 2.70); The same trial reported greater sports continuation in the mosaicplasty group at three years (25/28 versus 8/29; RR 3.24, 95% CI 1.77 to 5.92). Pooled data from two trials of participants with radiographically- defined osteoarthritis showed a significant difference in favour of mosaicplasty (9/40 versus 19/40; RR 0.48, 95% CI 0.25 to 0.92). Conclusion: Overall, there is a total lack of evidence about allograft transplantation or drilling and there is insufficient evidence to draw conclusions on the use of microfracture and mosaicplasty for treating isolated cartilage defects of the knee in adults in regards to function, quality of life, and activity. However, the "failure of treatment and adverse effects" and "quality of cartilage" was favorable for the mosaicplasty intervention. Due to the low evidence, further research is needed to define the best surgical option for treating isolated cartilage defects of the knee in adults.